2021
DOI: 10.1109/access.2021.3082423
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitivity Analysis of Biophysiological Responses of Stress for Wearable Sensors in Connected Health

Abstract: Stress is known as a silent killer that contributes to several life-threatening health conditions such as high blood pressure, heart disease, and diabetes. The current standard for stress evaluation is based on self-reported questionnaires and standardized stress scores. There is no gold standard to independently evaluate stress levels despite the availability of numerous biophysiological stress indicators. With an increasing interest in wearable health monitoring in recent years, several studies have explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…Similar to other studies [13][14] [15], that have reported previously we found that EDA, temperature, and accelerometer are important features in stress detection. Our objective was not to find one optimal feature, but multiple features that can help in precise detection.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to other studies [13][14] [15], that have reported previously we found that EDA, temperature, and accelerometer are important features in stress detection. Our objective was not to find one optimal feature, but multiple features that can help in precise detection.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, in a detailed literature survey and statistical analysis to determine the most sensitive and specific parameters for stress-monitoring, we concluded that the respiratory rate (RR) is the most important parameter for the detection of stress conditions [ 15 , 16 , 33 ]. The results of these statistical analyses were published in [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the lack of gold standard ground-truth/reference values or data, collection of stress data in the natural environment, different confounding variables, identification of discriminative/specific stress features, and development of an accurate classifier model to classify stress data from baseline/normal are also contributing reasons to the lack of unswerving stress monitoring device. Further details are explained in [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological parameters that are frequently used for stress analysis are respiratory rate, heart rate, skin conductance, skin temperature, and galvanic skin response ( 13 ). As supervised learning requires training labels for training the classifier, in most cases, either the labels are unavailable or inaccurate, in the real-time data collection ( 14 ).…”
Section: Introductionmentioning
confidence: 99%